PREMI RESTORNO DALAM PERJANJIAN ASURANSI - Marsidah, Marsidah (Faculty of Law, University of Palembang, 2020)
Premium is one of the obligations of the insured that must be paid to the insurer, but the paid premium can be asked back by the insured. The premium that the insured party asks to return is called the Restorno Premium. The problems in this paper are the things that can lead to the Restorno Premium by the insurance agreement. Restorno Premium is the repayment of insurance premiums from the insurer to the insured due to the failure / cancellation of the insurance agreement from the insured who has good faith as stipulated in Article 281 of the KUHD. In addition, the Restorno Premium can be fulfilled by the insurer if there are things mentioned in Article 251 of the Criminal Code, namely false or untrue information or not telling things that the insured knows about.